Recovery of high specific activity molybdenum-99 from accelerator-induced fission on low-enriched uranium for technetium-99m generators - M. Alex Brown (Nature Portfolio, 2021)
Abstract A new process was developed to recover high specific activity (no carrier added) 99Mo from electron-accelerator irradiated U3O8 or uranyl sulfate targets. The process leverages a novel solvent extraction scheme to recover Mo using di(2-ethylhexyl) phosphoric acid following uranium and transuranics removal with tri-n-butyl phosphate. An anion-exchange concentration column step provides a final purification, generating pure 99Mo intended for making 99Mo/99mTc generators. The process was demonstrated with irradiated uranium targets resulting in more than 95% 99Mo recovery and without presence of fission products or actinides in the product.